Implementasi Perencanaan Sekolah Berbasis Rapor Pendidikan - Purwadi , Dedy; Connie, Connie; Sumarsih (Manajer Pendididikan, 2025)
The purpose of the research is to find out the school planning based on the education report card, the implementation of school planning based on the education report card in the sc hool mover program, as well as the supporting and inhibiting factors for the implementation of school planning based on the education report card in the school program at the Sumber Harta State Junior High School, Musi Rawas Regency. This study uses a qualitative approach and a descriptive type of research. The data source of this research is the principal, vice president of curriculum, operator and teachers. Data collection techniques are in the form of interviews, observations, and documentation. Research results: 1). School planning based on education report cards is one of the best programs in SMP Negeri Sumber Harta to improve the quality of education. 2). The implementation of education report card-based planning in the implementation of school mover program at SMPN Sumber Harta has been well implemented by including aspects of problem identification, reflection, improvement, and activities. 3). Supporting factors in the implementation of education report card-based planning in the school mover program at SMP Negeri Sumber Harta include full support from the principal and school human resource management, data and information quality, and education policies. Meanwhile, the inhibiting factors include lack of training and skills, limited resources, inaccurate data, resistance to change, teaching and training tools